Studi Pengembangan Wilayah Kota Sukabumi - Noviar Pahlevi; Setia Hadi; Soekmana Soma (TATALOKA, 2014)
Sukabumi development approach which has been more emphasis on economic growth tends to ignore the regional disparities. Therefore, it is necessary to study and identify the direction of regional development policy . By knowing the level of disparity that occurred in this research sought leading sectors and the level of regional development to build of the Sukabumi city. The analytical method used is the Williamson index , Theil index , Location Quotient , Shift Share Analysis , Entropy and Schallogram . From the analysis  is known that there has been a disparities of Sukabumi areas in middle category / uneven . The development of the old town area which consists of a level hierarchy I and II have the balance of diversity and economic sectors better, the leading sector dominated by the tertiary sector which is urban characteristics . While the new city area, including the development of a hierarchy of regions III and leading sectors dominated by primary and secondary sectors which are characteristic of rural areas.Sukabumi development approach which has been more emphasis on economic growth tends to ignore the regional disparities. Therefore, it is necessary to study and identify the direction of regional development policy . By knowing the level of disparity that occurred in this research sought leading sectors and the level of regional development to build of the Sukabumi city. The analytical method used is the Williamson index , Theil index , Location Quotient , Shift Share Analysis , Entropy and Schallogram . From the analysis  is known that there has been a disparities of Sukabumi areas in middle category / uneven . The development of the old town area which consists of a level hierarchy I and II have the balance of diversity and economic sectors better, the leading sector dominated by the tertiary sector which is urban characteristics . While the new city area, including the development of a hierarchy of regions III and leading sectors dominated by primary and secondary sectors which are characteristic of rural areas.